Features of Social Adaptation of Teenagers from Families of Migrant Workers - Lyzun, Iryna (Pedagogical Discourse, 2012)
The article deals with the main features of the social adaptation of teenagers from families of migrant workers. The stages, which the teenager passes at a time of acquaintance with new social environment are defined.